Comunicação científica na Arquivologia: reflexões sobre os temas mais incidentes e da produtividade nos periódicos na área - BARROS, Diogo Júnior Silva (2017)
Scientific journals are important tools in the process of scientific communication, thus this study aims to quantitatively analyze Archival Science productions from magazines Collection, Agora, Archival Information and Online Archeion considered specific field currently in activity. The research has the following objectives: to raise the issues of indexes treated in the Brazilian Archival Science journals through keywords, identify specific journals Archival Science, identify changes and continuities in scientific communication Archival Science, identify the five most productive authors and discuss the results analyzed by bibliometric techniques. Previous studies, such as José Maria Jardim and Jayme Vilan Filho, were also considered for purposes of comparison about the changes in archival context in Brazil over the years. The results obtained allowed to identify a significant increase in publications, a majority of teachers authors and doctors, author of publications in accordance with the Law of Lotka, significant presence of librarians and foreigners among the most productive authors and the lack of specific journals Archival Science in Brazil.